Trends in the Development of Augmented Reality Research in Elementary Schools in Science Learning: A Bibliometric Analysis - Ifa Safira; Fathia Azzahra; Rohmani (Universitas Pendidikan Ganesha, 2025)
Science learning in elementary schools often faces challenges in helping students understand abstract concepts in an engaging and interactive way. This study aims to analyze trends in publications related to the use of Augmented Reality (AR) in elementary science learning and to visualize research developments in this field. The study employs a descriptive bibliometric analysis, with data sourced from the Scopus database. The research stages include identification, screening, eligibility, and inclusion, resulting in 66 articles that met the inclusion criteria. The analysis shows that AR research in science learning has been conducted widely, with the most frequent keywords being “Augmented Reality,” “Elementary School,” and “Science Learning.” Furthermore, emerging promising themes include educational computing, educational games, and 3D animation. Publication trends indicate a decline in the number of articles in recent years, although certain earlier years had significant influence on the development of research in this field. The study concludes that AR has great potential to enhance student engagement, clarify concept understanding, and develop 21st century skills. The implications of this research highlight the importance of further exploration of AR applications in science learning, as well as opportunities for innovative research on emerging themes.